Advanced glycation end products, their receptor and the risk of dementia in the general population: A prospective cohort study: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - Chen, Jinluan; Mooldijk, Sanne S.; Licher, Silvan; Waqaz, Komal; Ikram, M. Kamran; Uitterlinden, André G.; Zillikens, M. Carola
Abstract: Background: Advanced glycation end products (AGEs) and their receptor (RAGE) are implicated in the pathophysiology of dementia and potentially underlie the relation between diabetes and neurodegeneration. We determined the link between two proteins involved in the AGE‐RAGE system, namely Extracellular Newly identified RAGE binding protein (EN‐RAGE) and the soluble form of RAGE (sRAGE), and dementia prevalence and incidence. Additionally, we assessed the association between skin auto fluorescence (SAF), a proxy for AGEs tissue accumulation, and cognition. Method: Within the prospective Rotterdam Study, plasma EN‐RAGE and sRAGE were measured in 1208 participants (mean age 74.1 (standard deviation (SD) 7.7); 57.5% women). Participants were categorized into tertiles, to compare participants with high, intermediate and low concentrations, with the lowest tertile as the reference. Associations of SAF, measured in 3009 participants (mean age 72.3 (SD 9.4); 56.4% women), and cognition were assessed using linear models. We adjusted for age, sex, diabetes, APOE ε4 carrier status and other potential confounders, including cardiovascular risk factors, and additionally stratified by sex and APOE ε4 status. Result: Participants with higher EN‐RAGE and lower sRAGE levels were more likely to have dementia (adjusted odds ratio (OR); 3.64 [95% confidence interval 1.56‐8.50] and OR 0.39 [0.17‐0.83], for high level compared to low level). During follow‐up (median 12.4 years), 161 participants developed dementia, of whom 130 Alzheimer's disease (AD). Higher EN‐RAGE was non‐significantly associated with higher risk of dementia during the first years of follow‐up (adjusted hazard ratio (HR); 1.48 [0.52‐4.25] after 4 years of follow‐up), while a lower risk was found over the entire follow‐up duration (HR 0.65 [0.42‐1.01]) (Figure 1). Higher SAF was associated with lower global cognitive function (adjusted difference in z score per SAF standard deviation (SD); 0.07 [0.04‐0.11]). This effect was stronger for carriers of the APOE ε4 allele (0.15 [0.07‐0.22]). Conclusion: Our results indicate involvement of the AGE‐RAGE system in the pathophysiology of dementia, independent of the history of diabetes, showing involvement of EN‐RAGE and sRAGE, and of SAF in cognitive functioning. These associations were stronger for APOE ε4 carriers, suggesting a combined role of AGEs and APOE in neurodegeneration.